Spatial Clustering of Electricity Consumption Patterns in Indonesian Higher Education Institutions (Faculty of Engineering, Universitas Tanjungpura, 2026)
Higher education institutions represent a significant contributor to electricity consumption in the public sector, particularly in developing countries such as Indonesia. This study aims to identify spatial patterns and provincial disparities in electricity consumption across Indonesian higher education institutions. This research method uses spatial autocorrelation analysis with Moran's I and hierarchical clustering based on Ward’s method. The results show that the observed Moran’s I (0.5129679) is higher than the expected Moran’s I (-0.03030303), and the spatial pattern of electricity consumption by higher education institutions is clustered. This result is confirmed by the negligible p-value (0.0003618787 < 0.05), indicating a strong clustered spatial pattern. Hierarchical clustering was used to identify three groups of provinces representing the level of electricity consumption. The findings highlight significant regional disparities in electricity consumption patterns and provide a quantitative basis for energy management strategies and sustainable higher education policy planning in Indonesia.